Structure & Causes of Illegal Medicines Circulation in Indonesia - Imam Luqman Hakim; Yos Sunitiyoso (Journal of International Conference Proceedings, 2021)
The circulation of illegal medicines in Indonesia is still happening. Illegal in this case because the product does not have a distribution permit, is counterfeit, or circulated without the authority as regulated by regulations. The limitation in this study is devoted to discussing the phenomenon of the circulation of illegal medicines that have a psychoactive effect which is vulnerable to abuse, consumed for specific purposes other than medical purposes, and even without a physician's recommendation. This study aims to understand the process, structure, and determinants of the circulation of illegal medicines vulnerable to abuse in Indonesia with system dynamic approach. The data were obtained from an exploratory study which included a literature review, field observations, and in-depth interviews then made a rich picture diagram and a causal loop diagram among the determinants of the circulation of illegal medicines that are vulnerable to abuse. Furthermore, the interpretation of the complexity of the structure that is formed is carried out. The study results indicate six categories, 47 factors, and nine loops that are the determinants of the circulation of illegal medicines that are vulnerable to abuse in Indonesia. Therefore, this study can contribute to knowledge about the complex structure and main determinants of the circulation of illegal medicines vulnerable to abuse in Indonesia and support efforts to reduce this illegal activity.